Hyperglycemia Induced Hemichoreoathetosis, An Uncommon Presenting Symptom of Diabetes Mellitus - Sethu Prabhu Shankar; Neelakandan Ramya; Gopalakrishnan Vikraman; Ratchagan Saravanan (Acta Medica Iranica, 2012)
Chorea is brief, quasi-purposeful, irregular muscle contractions, not repetitive or rhythmic, but flows from one muscle to the next and athetosis is slow, writhing, continuous, worm-like movements of distal extremities (chiefly the fingers) which show bizarre positioning without posturing. Metabolic causes have been documented earlier, note worthy of that being Diabetes. Choreoathetosis has been reported earlier in diabetes mostly in an elderly female, diagnosed most often by Brain MRI. We report a case of hemichoreoathetosis in a male diabetic, whose involuntary movement completely resolved with glycemic control and diagnosis was easily confirmed with just a Brain CT.